Reproductive biology and feeding habits of the prickly dogfish Oxynotus bruniensis. Issue 5 (8th September 2016) - Finucci, B.; Bustamante, C.; Jones, E. G.; Dunn, M. R.
Abstract : The reproductive biology and diet of prickly dogfish Oxynotus bruniensis, a deep‐sea elasmobranch, endemic to the outer continental and insular shelves of southern Australia and New Zealand, and caught as by‐catch in demersal fisheries, are described from specimens caught in New Zealand waters. A total of 53 specimens were obtained from research surveys and commercial fisheries, including juveniles and adults ranging in size from 33·5 to 75·6 cm total length ( L T ). Estimated size‐at‐maturity was 54·7 cm L T in males and 64·0 cm L T in females. Three gravid females (65·0, 67·5 and 71·2 cm L T ) were observed, all with eight embryos. Size‐at‐birth was estimated to be 25–27 cm L T . Vitellogenesis was not concurrent with embryo development. Analysis of diet from stomach contents, including DNA identification of prey using the mitochondrial genes cox 1 and nadh 2, revealed that O. bruniensis preys exclusively on the egg capsules of holocephalans, potentially making it the only known elasmobranch with a diet reliant solely upon other chondrichthyans. Based on spatial overlap with deep‐sea fisheries, a highly specialized diet, and reproductive characteristics representative of a low productivity fish, the commercial fisheries by‐catch of O. bruniensis may put this species at relatively high risk of overfishing.